Spontaneous Intraperitoneal Bladder Rupture with Normal Renal Indices. A Case Report of Unusual, Confusing Presentation - Ibrahim, Mohammed Abdulkareem; Salah, Morshed Ali (Archives of Clinical and Medical Case Reports, 2022)
Background: Spontaneous Bladder Rupture (SBR) is one of the rare causes of acute abdomen seen in the emergency room. Almost all the reported cases of atraumatic intraperitoneal bladder rupture were associated with a state of pseudo- acute kidney injury due to resorption of leaked urine urea and creatinine through peritoneum to the blood. Case Presentation: 25-year old lady. Presented with few hours history of sudden attack of severe lower abdominal pain associated with nausea, no vomiting, with increasing abdominal distention, no history of trauma. Vital signs were stable; however, blood pressure was decreasing. Local abdominal examination showed generalized abdominal tenderness, rigidity and guarding. Labs showed normal renal indices as well as the inflammatory parameters. The patient reported history of TURBT for a single, small PUNLMP bladder tumor 10-months before her presentation. Abdomen CT finding, Retrograde cystogram, flexible cystoscope then exploratory laparotomy confirmed the diagnosis of intraperitoneal bladder rupture. The patient went through smooth post-operative and follow up course. Conclusion: Intraperitoneal (SBR) still could be considered as one of the serious causes of acute abdominal condition even in the absence of elevated renal indices with strong emphasis on the history of previous bladder intervention.